The effects of methyl donors and modulated methyl group status on health and performance in growing cattle - Grant, Madeline Sue (Kansas State University, 2020)
Two experiments were conducted to evaluate the effects of methyl donor supplementation to growing cattle. In the first experiment, 384 crossbred heifers (222 kg initial BW) were utilized to study effects of methionine supplementation on high-risk receiving cattle. Heifers were limit-fed at 2.2% BW daily a corn- and corn-byproduct-based diet and supplemented with 0 (control) or 10 g/d Smartamine M to provide 6 g/d metabolizable methionine. Pen weights were collected weekly to determine feed offerings the following week. Individual BW and tail-vein blood samples were collected on d 0, 14, and 45. Plasma haptoglobin was measured to assess inflammatory status. Incidences of morbidity (1.6% for control, 2.6% for SM) and mortality (0.5% for both control and SM) were low. Between d 0 and 45, no differences were observed for ADG or G:F (P ≥ 0.28). An interaction between treatment and linear effect of day was detected for plasma haptoglobin (P = 0.05); over time haptoglobin increased more for control than for SM. In the second study, six ruminally cannulated Holstein steers (200 kg) were used in a 6 × 6 Latin square design with 10-d periods to evaluate the effects of modulated methyl group status on protein deposition and immune function. Factorial treatments included 3 methyl group modulators (MGM: control; 15 g/d guanidinoacetic acid [GAA]; or 16.8 g/d creatine) and 2 levels of choline (0 or 5 g/d choline ion); treatments were continuously infused abomasally. Providing GAA or creatine increases body creatine supply, but GAA will consume methyl groups to synthesize creatine, whereas supplemental creatine spares methyl groups otherwise used for its synthesis. Total fecal and urine collections occurred from d 7 to 9 to measure N balance and jugular blood was collected on d 10. No interactions between MGM and choline were observed. GAA increased N retention (P = 0.04), whereas creatine did not (P = 0.56). Plasma and urinary creatine were increased by GAA and creatine (P ≤ 0.01), with GAA leading to a larger increase. No effects of MGM on plasma haptoglobin (P = 0.97) or ex vivo neutrophil oxidative burst or phagocytosis (P ≥ 0.30) were observed, but creatine did reduce plasma antioxidant capacity (P ≤ 0.01). Choline did not affect N retention (P = 0.69) but increased plasma creatine (P = 0.04). Choline tended to reduce plasma haptoglobin (P = 0.07) but did not affect antioxidant capacity. Choline tended to reduce neutrophil phagocytosis in the presence of LPS (P = 0.09) but did not affect neutrophil phagocytosis in absence of LPS or neutrophil oxidative burst in the presence or absence of LPS (P ≥ 0.29). These data demonstrate that GAA has potential to improve protein deposition in growing cattle fed corn-based diets. Also, choline may improve body creatine status and alter neutrophil function. Overall, methionine and choline appear to mitigate inflammation in growing cattle.
Keywords: Methyl group; Methionine; Choline; Guanidinoacetic acid; Immune function; Cattle